Template determines whether chemically identical nanoparticle scaffolds show elastic recovery or plastic failure - Suresh, Karthika; Patil, Shivprasad; Rajamohanan, Pattuparambil Ramanpillai; Kumaraswamy, Guruswamy (Langmuir, 2016)
Subtle variations in the preparation of ice-templated nanoparticle assemblies yield monoliths that are chemically identical but exhibit qualitatively different mechanical behavior. We ice template aqueous dispersions to prepare macroporous monoliths largely comprising silica nanoparticles held together by a crosslinked polymer mesh. When the polymer is crosslinked in the presence of ice crystals, we obtain an elastic sponge that is capable of recovery after imposition of large compressive strains (up to 80%). If, however, the ice is lyophilized before the polymer is crosslinked, we obtain a plastic monolith that fails even for modest strains (less than 10%). The elastic sponge and the plastic monolith are chemically identical; they have the same organic content, the same ratio of polymer to crosslinker, and the same average crosslink density. Atomic force microscopy (AFM) was used to probe the local mechanical properties of the crosslinked polymer mesh. These measurements indicate that plastic monoliths dissipate significantly more energy and have a larger spatial variation in local mechanical response relative to the elastic sponges. We believe that this behavior might correlate with a wider spatial distribution of crosslinks in plastic scaffolds relative to elastic scaffolds.

Convergent covalent organic framework thin sheets as flexible supercapacitor electrodes - Khayum, Abdul M.; Vijayakumar, Vidyanand; Karak, Suvendu; Kandambeth, Sharath; Bhadra, Mohitosh; Suresh, Karthika; Acharambath, Nikhil; Kurungot, Sreekumar; Banerjee, Rahul (ACS Applied Material & Interfaces, 2018)
Flexible supercapacitors in modern electronic equipment require light-weight electrodes, which have a high surface area, precisely integrated redox moieties, and mechanically strong flexible free-standing nature. However, the incorporation of the aforementioned properties into a single electrode remains a great task. Herein, we could overcome these challenges by a facile and scalable synthesis of the convergent covalent organic framework (COF) free-standing flexible thin sheets through solid-state molecular baking strategy. Here, redox-active anthraquinone (Dq) and pi-electron-rich anthracene (Da) are judiciously selected as two different linkers in a beta-ketoenamine-linked two-dimensional (2D) COF. As a result of precisely integrated anthraquinone moieties, COF thin sheet exhibits redox activity. Meanwhile, pi-electron-rich anthracene linker assists to improve the mechanical property of the free-standing thin sheet through the enhancement of noncovalent interaction between crystallites. This binder-free strategy offers the togetherness of crystallinity and flexibility in 2D COF thin sheets. Also, the synthesized porous crystalline convergent COF thin sheets are benefited with crack-free uniform surface and light-weight nature. Further, to demonstrate the practical utility of the material as an electrode in energy-storage systems, we fabricated a solid-state symmetrical flexible COF supercapacitor device using a GRAFOIL peeled carbon tape as the current collector.

Functionalized carbon nanotube reinforced polymer nanocomposite microcapsules with enhanced stiffness - Jagtap, Siddheshwar B.; Patil, Vishal D.; Suresh, Karthika; Ram, Farsa; Mohan, Muthu Subramanian; Rajput, Shatruhan S.; Patil, Shivprasad; Shukla, Parshuram G.; Shanmuganathan, Kadhiravan (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2018)
Microcapsules with tunable mechanical properties are highly desirable in pressure sensitive applications. We report here a facile approach to prepare polyurea/multiwall carbon nanotube (MWCNTs) nanocomposite microcapsules (MICs) with enhanced stiffness. A model compound dimethyl phthalate (DMP) was used as core material. MWCNTs were modified with reactive functional groups namely carboxyl (-COOH), amines (-NH2), and isocyanates (-NCO) to ensure a stronger interface between polymer wall and MWCNTs. Functionalization of MWCNTs was corroborated by Fourier transformed infrared spectroscopy (FTIR). Scanning electron microscopy (SEM) was employed to study the surface morphology of MICs. The presence of MWCNTs in the microcapsule wall was confirmed by transmission electron microscopy (TEM). MICs with functionalized MWCNTs show almost 100% increase in stiffness with respect to pristine capsules. All MICs show 92-97 +/- 1% encapsulation efficiency. The approach used in this paper can be broadly utilized to tune the mechanical properties of the microcapsules.

Single-particle tracking to probe the local environment in ice-templated crosslinked colloidal assemblies - Suresh, Karthika; Sharma, D. K.; Chulliyil, Ramya; Sarode, Ketan Dinkar; Kumar, V. Ravi; Choudhary, Arindam; Kumaraswamy, Guruswamy (Langmuir, 2018)
We use single-particle tracking to investigate colloidal dynamics in hybrid assemblies comprising colloids enmeshed in a crosslinked polymer network. These assemblies are prepared using ice templating and are macroporous monolithic structures. We investigate microstructure-property relations in assemblies that appear chemically identical but show qualitatively different mechanical response. Specifically, we contrast elastic assemblies that can recover from large compressive deformations with plastic assemblies that fail on being compressed. Particle tracking provides insights into the microstructural differences that underlie the different mechanical response of elastic and plastic assemblies. Since colloidal motions in these assemblies are sluggish, particle tracking is especially sensitive to imaging artifacts such as stage drift. We demonstrate that the use of wavelet transforms applied to trajectories of probe particles from fluorescence microscopy eliminates stage drift, allowing a spatial resolution of about 2 nm. In elastic and plastic scaffolds, probe particles are surrounded by other particles—thus, their motion is caged. We present mean square displacement and van Hove distributions for particle motions and demonstrate that plastic assemblies are characterized by significantly larger spatial heterogeneity when compared with the elastic sponges. In elastic assemblies, particle diffusivities are peaked around a mean value, whereas in plastic assemblies, there is a wide distribution of diffusivities with no clear peak. Both elastic and plastic assemblies show a frequency independent solid modulus from particle tracking microrheology. Here too, there is a much wider distribution of modulus values for plastic scaffolds as compared to elastic, in contrast to bulk rheological measurements where both assemblies exhibit a similar response. We interpret our results in terms of the spatial distribution of crosslinks in the polymer mesh in the colloidal assemblies.

Critical role of processing on the mechanical properties of cross-linked highly loaded nanocomposites - Suresh, Karthika; Chowdhury, Arindam; Kumar, Sanat K.; Kumaraswamy, Guruswamy (Macromolecules, 2019)
Polymer nanocomposites are frequently not at equilibrium-therefore, the structure and properties critically depend on the protocol followed in their preparation. Here, we demonstrate that the elastic-brittle transition in highly loaded ice-templated polymer nanocomposites is sensitively determined by the conformation of polymer chains during nanocomposite preparation. Macroporous polymer nanocomposites are synthesized using two preparation pathways, both exhibiting minor modifications of the ice-templating method wherein an aqueous dispersion of nanoparticles, polymers, and cross-linkers is frozen. In one method, the matrix polymer is cross-linked in the presence of ice, whereas in the other method, the ice is removed by freeze-drying before the polymer is cross-linked. Although all measurable structural metrics are practically identical for the two composites, they exhibit qualitatively different mechanical properties. Nanocomposites cross-linked in the presence of ice show exceptional resilience, recovering elastically from large compression for very high nanoparticle loadings-in some instances, above 90% by weight. Here, the critical particle loading for the elastic- brittle transition is dependent on the molecular weight of the polymer. In comparison, samples cross-linked after freeze-drying appear structurally identical but turn brittle at much lower particle loadings (about 60% by weight), independent of the matrix polymer molecular weight. We rationalize these differences in terms of the conformational state of the polymer during cross- linking. In the former case, polymer chains are in good solvent during nanocomposite preparation, while after lyophilization, they are in a poor solvent. The large spatial extent of well-solvated chains and chain-chain overlap during cross-linking results in the formation of intermolecular cross-links, and we obtain elastic nanocomposites even at high nanoparticle loadings. In contrast, for chains in collapsed conformations in a bad solvent, chain connectivity during cross-linking is achieved only for much lower particle loadings. Our results reiterate that the sensitivity of polymer conformations to different processing methods can result in large differences in properties, even though their consequences on structural characteristics are effectively indistinguishable.

Effect of electrostatic interactions on structure and mechanical properties of ice templated colloid-polymer composites - Suresh, Karthika; Kumaraswamy, Guruswamy (Journal of Physics D-Applied Physics, 2019)
When an aqueous dispersion of negatively charged colloids, cationic polymer and crosslinker is frozen and the polymer is allowed to crosslink in the frozen state, we obtain a self-standing macroporous composite foam. This material is soft, despite the high concentration of colloids and yet is remarkably elastic to large compressive strains. In these macroporous composites, the pore walls comprise colloidal particles held within a crosslinked polymer network. Here, we investigate the effect of varying colloid- polymer interactions in pre-fabricated macroporous composites on their microstructure and mechanical properties. During preparation of the composite, cationic polymer adsorbs on the negatively charged colloids. We tune the surface charge of particles embedded in a macroscopic monolith by immersing the composites in water maintained at different pH. In this way, we tune polymer-particle interactions in the composite. We observe a sudden increase in interparticle distance and swelling of composite when pH is decreased below the particle's isoelectric point. Correspondingly, we observe reduction in Young's and shear moduli, compression strength and macroscopic energy dissipation. We did not observe any pH dependent changes in pure polymer sponges (prepared by ice templating and crosslinking a polymer solution that does not contain colloidal particles). Therefore, the pH dependent structural and mechanical property changes arise from the composite structure rather than purely from the crosslinked polymer. We believe that the reduction in mechanical stiffness when the polymer-particle interaction becomes repulsive is because of the reduction in interfacial contacts between particle and polymer. Therefore, the mechanical stiffness of ice templated composite is strongly influenced by interactions between the polymer and particle surface.
Keywords: colloid; electrostatic interaction; ice templating; mechanical properties; Polymer

On the sensitivity of alginate rheology to composition - Suresh, Karthika; Haering, Marleen; Kumaraswamy, Guruswamy; Diaz Diaz, David (Soft Matter, 2019)
The linear response of alginate-phenyl boronic acid (Alg-PBA) esters shows a universal, composition-independent viscoelastic fluid-like behaviour. Reversible association of alginates governs their rheology at all compositions (viz. at all alginate concentrations and solution pH). However, their high strain behaviour is very sensitive to composition. Tuning composition affords liquids that neck to form filaments capable of being drawn to large elongations without failure. We interpret our data by invoking strain-dependent association and dissociation rates for the alginates. High association rates at high strain result in materials with viscoelastic liquid like behaviour.

Ice templated nanocomposites containing rod-like hematite particles: Interplay between particle anisotropy and particle-matrix interactions - Kumaraswamy, Guruswamy; Suresh, Karthika; Lama, Hisay; Basavaraj, Madivala G.; Satapathy, Dillip K. (Journal of Applied Physics, 2020)
We demonstrate that the mechanical response of ice templated nanocomposite scaffolds prepared from ellipsoidal hematite particles is determined by both the particle aspect ratio and the interaction between the particles and the matrix polymer. We ice template aqueous dispersions of hematite particles, polyethyleneimine, and diepoxy crosslinker and crosslink the polymer in the frozen state. This protocol results in the formation of elastic macroporous monoliths capable of complete recovery from large compressive strains. Hematite particles show an inversion of their surface charge with pH: they are negatively charged at a basic pH and positively charged under acidic conditions. This allows us to change the interaction between hematite particles and crosslinked matrix polymer that they are embedded in, simply by immersing the monoliths in aqueous solutions with different pH's. We report that under basic conditions, viz, when polyethyleneimine adsorbs on the particle surface, there is a decrease in the monolith modulus with an increase in the particle aspect ratio. We demonstrate that this correlates with a change in the mechanism of monolith response: from wall compression for isotropic particles to wall bending for anisotropic particles with an aspect ratio of 4. Under acidic conditions (pH=2), where hematite particles show a positive zeta potential, the monolith modulus increases with the aspect ratio of the ellipsoidal fillers. Understanding the interplay between filler aspect ratio and filler-matrix interaction has important implications for the control of nanocomposite mechanical properties.

Highly compressible ceramic/polymer aerogel-based piezoelectric nanogenerators with enhanced mechanical energy harvesting property - Ram, Farsa; Suresh, Karthika; Torris, Arun; Kumaraswamy, Guruswamy; Shanmuganathan, Kadhiravan (Ceramics International, 2021)
Ceramic piezoelectric materials have orders of magnitude higher piezoelectric coefficients compared to polymers. However, their brittleness precludes imposition of large strains in mechanical energy harvesting applications. We report here that ice templating affords low bulk modulus lead-free aerogel piezoelectric nanogenerators (PENG) with unprecedented combination of flexibility and high piezoelectric response (voltage and power density). A modified ice templating protocol was used to fabricate piezoelectric nanocomposites of surface modified BaTiO3 (BTO) nanoparticles in crosslinked polyethylene imine. This protocol allowed incorporating a significantly high fraction of BTO particles (up to 83 wt %) in the aerogel, while retaining remarkably high compressibility and elastic recovery up to 80% strain. The output voltage, at an applied compressive force of 20 N (100 kPa), increased with BTO loading and a maximum output voltage of 11.6 V and power density of 7.22 ?W/cm2 (49.79 ?W/cm3) was obtained for PENG aerogels containing 83 wt% BTO, which is orders of magnitude higher than previously reported values for foam-based piezoelectric energy harvesters. The BTO/PEI PENGs also showed cyclic stability over 900 cycles of deformation. PENGs with higher porosity showed better elastic recovery and piezoelectric properties than lower porosity and higher BTO content aerogels. To the best of our knowledge, this is the first report to demonstrate the piezoelectric properties of high ceramic content aerogels having very high compressibility and elastic recovery.
Keywords: Ceramic polymer aerogels; energy harvesting; ice templating; piezoelectric

Dual-mode porous and highly graphitized 3D nitrogen-doped carbon network as an advance anode material for sodium-ion batteries - Dar, Mudasir; Suresh, Karthika; Majid, Kowsar; Wahid, Malik (Journal of Physical Chemistry C, 2023)
The practical application of hard carbons as the mostappealinganode material for sodium-ion batteries is hampered by their poorcycling and rate performances, emanating from poor electrochemicalstability, low electroconductivity, and sluggish Na+ transport.Designing a single remedial method for these challenges often involvescomplex and energy-intensive processes, contradicting the core conceptof cost-effectiveness for practical energy storage technology. Herein,we employed trifunctional silica (SiO2): as colloidal silicato ice template micron-sized pores, as a hard template for nanopores,and as a catalyst for the graphitization of carbon for the synthesisof a highly graphitized, efficiently nitrogen-doped, high-surface-area,three-dimensional porous carbon network (3D PNC) with dual-mode porosity(nanopores and micron-sized pores). As an anode material, the obtained3D PNC exhibits a reversible capacity of 262 mAh g(-1) at a current density of 100 mA g(-1), an ultrahighrate capability of 173 mAh g(-1) at 1 A g(-1), and a stable cycling life of 1000 cycles at a high current densityof 100 mA g(-1) with almost 100% capacity retention.The galvanostatic intermittent titration technique (GITT) revealsfacile sodium diffusion kinetics with an average diffusion coefficientof an order of & SIM;10(-9) (cm(2) s(-1)), which is fairly low compared to most reported HCanodes for SIBs. This work demonstrates how a merger of two or moresynthesis methodologies can be employed for the advanced microstructureengineering of carbon materials, opening up new avenues for the rationaldesign of anode materials in SIBs.